ANALISIS KONSEPTUAL TERHADAP FONDASI EKONOMI MAKRO ISLAM: STUDI LITERATUR - Randi Muhammad Irawan; Ronal Jusupan Maulana, Suci Hayati (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to conceptually analyse the foundations of macroeconomics from an Islamic perspective through a library research approach. Islamic macroeconomics is part of the Islamic economic system that emphasises the values of justice, balance, and holistic welfare (falah) for the people. Unlike conventional economics, which is oriented towards growth and efficiency alone, Islamic economics incorporates moral, social, and spiritual elements into economic management. This study found that basic principles such as the prohibition of usury, fair distribution of wealth, and the importance of the state's role in maintaining economic balance are the main foundations of Islamic macroeconomics. Additionally, instruments such as zakat, infak, sedekah, wakaf, and baitul mal play a crucial role in creating a just and sustainable economic system. The findings of this study are expected to enrich the body of knowledge in Islamic economics and serve as a foundation for further applied research.